Why are small firms different? - Agell, Jonas (Univ., Center for Economic Studies [u.a.], 2003)
Do incentives in small organizations differ from those in large ones? This paper uses a representative survey of compensation managers to shed light on the issues. I find that (i) small establishments rely less on pecuniary incentives, and have a significantly more hostile attitude towards incentive schemes based on competition and relative rewards; (ii) large units are more vulnerable to mechanisms of efficiency wages, effects that remain even as I control for differences in monitoring ability; (iii) large units are more prone to indicate that negative reciprocity is important, and that their employees care about relative pay. I argue that these findings fit with behavioral stories of incentives and motivation, in particular those stressing group interaction effects, inequity aversion and gift exchange.
Internetausg.: http://www.cesifo.de/pls/ifo_app/DocLinkCESifoDl?getDoc=cesifo1_wp1076.pdf
Keywords: Arbeitspapier; Graue Literatur; Betriebsgröße; KMU; Motivation; USA; Business enterprises; Incentives in industry; Small business; Wage surveys; Wages